2022
DOI: 10.1155/2022/9927805
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Skin-to-Skin Contact on Postoperative Depression and Physical Recovery of Parturients after Cesarean Section in Obstetrics and Gynecology Department

Abstract: The effect of skin-to-skin contact (SSC) on postpartum depression and physical rehabilitation of cesarean section women was explored. 280 parturients undergoing cesarean section were selected and were rolled into two groups randomly. The parturients in the control group (Con group, 140 cases) received routine care, and those in the experimental group (Exp group, 140 cases) received SSC on the basis of routine care. The postpartum depression and physical recovery of parturients in two groups were compared. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Financial hardship faced by poor women in our study could affect post-discharge follow-up and care, and in turn could impede their ability to recover fully. Moreover, financial stress in low-income households are known to elevate the risk of postpartum depression [ 55 , 56 ], which also affects postoperative recovery [ 57 , 58 ]. Thus, interventions to mitigate financial hardships should be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Financial hardship faced by poor women in our study could affect post-discharge follow-up and care, and in turn could impede their ability to recover fully. Moreover, financial stress in low-income households are known to elevate the risk of postpartum depression [ 55 , 56 ], which also affects postoperative recovery [ 57 , 58 ]. Thus, interventions to mitigate financial hardships should be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…With the study [4] only stating that earlier skin-to-skin contact was achieved in 72% of cases and the study [5] only stating that the median time to first skin-to-skin contact was three minutes with the family-centered method, it is our understanding that no prior studies have described the difference in time for skinto-skin contact between methods. Among a few research, it was revealed that skin-to-skin contact might significantly reduce chronic uterine inflammation and postpartum discomfort, promote lactation, enhance blood flow restriction, and decrease postpartum depression in uterine parturient [19].…”
Section: Discussionmentioning
confidence: 99%
“…Depression is an a ective disorder. Its main clinical manifestations are long-term depression, loss of interest in many things, insomnia, and even self-mutilation [1][2][3][4]. According to the data released by the World Health Organization, there are about 340 million patients with depression in the world, with a prevalence rate of 35%.…”
Section: Background Introductionmentioning
confidence: 99%